Bacillus subtilis as a bioindicator to estimate pentachlorophenol toxicity and concentration - Ayude, M. A. (2009)
Pentachlorophenol (PCP) and its sodium salt (Na-PCP) are extremely toxic chemicals responsible for important soil and groundwater pollution, mainly caused by wastes from wood-treatment plants, because chlorinated phenols are widely used as wood preservatives. The methods most commonly used for routine analysis of pesticides such as PCP and Na-PCP are high-performance liquid chromatography (HPLC) and gas chromatography– mass spectroscopy (GC–MS). A variety of rapid biological screening tests using marine organisms, bioluminescent bacteria, and enzymes have also been reported. In this study, rapid biological screening analysis using Bacillus subtilis was developed, to assess the biodegradation of PCP and its by-products in liquid samples. An empirical model is proposed for spectrophotometric analysis of Na-PCP concentration after growth of Bacillus subtilis.